Invisible Presence: The Whitening of the Black Community in the Historical Imagination of British Archives - Bressey, Caroline (Archivaria, 2006)
The aim of this paper is to highlight the methods and ironies of researching Black histories in a British context. It is an attempt to expose tensions between the presence of Black people in London, their material presence in the archives available to researchers, and the complexities of British histories that their presence articulates. RÉSUMÉ Le but de ce texte est de mettre en évidence les méthodes et les ironies de la recherche des histoires noires dans un contexte britannique. Il tente d’exposer les tensions entre la présence des personnes de race noire à Londres, leur présence matérielle dans les archives disponibles pour les chercheurs, et les complexités des histoires britanniques dans lesquelles leur présence est exprimée.